Establishment of Vero cell-adapted thermostable candidate Newcastle Disease vaccine strain - Kabir, Md Humayun; Hasan, Md Amirul; Miyaoka, Yu; Yamaguchi, Makiko; Kadota, Chisaki; Shoham, Dany; Murakami, Harumi; Takehara, Kazuaki (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The current study aims to determine a thermostable Avian Orthoavulavirus 1 (AOaV1) or Newcastle disease (ND) vaccine candidate strain isolated from a duck and its adaptation to Vero cells. Material and Methods: From field isolates of AOaV-1 in Japan, avirulent APMV/northern pintail/ Japan/Aomori/2003 (dk-Amori/03, AOaV-1-261) was selected for its excellent thermostability, and the strain was heat treated at 56°C for 30 min during each passage into Vero cells to maintain thermostability and to adapt to Vero cells up to 20 passages, then named AOaV-1-Vero20. Growth curves were tested in Vero cells in comparison to the original AOaV-1-261. The intracerebral pathogenicity index (ICPI) test was done. The thermostability of the virus was checked at different temperatures. Serum neutralization test was done to check the induced levels of antibodies of the candidate vaccine strain in chicks. Sequencing of the HN and F genes and complete genome sequencing of the strains were done. Results: AOaV-1-Vero20 grew well on Vero cells compared to the original AOaV-1-261. The ICPI test score was 0. Minimum titer drops were found in the thermostability test. Induced, adequate levels of antibodies were measured using the serum neutralization test. Sequencing of the HN gene also revealed transmembrane domains, including 315 and 369 amino acid residues, with the same amino acids as those found in other thermostable strains. The sequence analysis results showed no significant variance in the whole genome sequences of AOaV-1-Vero20 and the original AOaV-1-261. Conclusion: In this study, AOaV-1-Vero20 was identified as a candidate vaccine strain that is thermostable, Vero cell-adapted, and has immunogenic potential. J. Adv. Vet. Anim. Res., 12(3): 1001–1011, September 2025 http://doi.org/10.5455/javar.2025.l959